Automated epileptic seizure detection based on break of excitation/inhibition balance. (April 2019) - Fan, Xiaoya; Gaspard, Nicolas; Legros, Benjamin; Lucchetti, Federico; Ercek, Rudy; Nonclercq, Antoine
Abstract: Physiological models are attractive for seizure detection, as their parameters are related to physiological meanings. We propose an algorithm to early detect epileptic seizures based on automatic estimation of average synaptic gains (excitatory Ae, slow and fast inhibitory B and G) by combining clinical data with a neural mass model. Three indices (Ae/B, Ae/G and Ae/(B + G)), all related to excitation/inhibition balance, were calculated and used as cues to detect seizures. A simple thresholding method was employed. We evaluated the algorithm against the manual scoring of a human expert on intracranial EEG samples from 23 patients suffering from different types of epilepsy. Best performance was achieved using Ae/(B + G) as a cue, i.e. excitation/(slow + fast) inhibition, on temporal lobe epilepsy (TLE) patients. A leave-one-out cross-validation showed that the algorithm achieved 92.98% sensitivity for TLE patients. The median false positive rate was 0.16 per hour, and median detection delay was 14.5 s. Of interest, the threshold values determined by a leave-one-out cross-validation did nearly not vary among TLE patients, suggesting a general excitation/inhibition balance baseline in TLE patients. The same approach could be used with other types of epilepsy by adapting the neural mass model to these types. Graphical abstract: Image 1 Highlights: Seizures can be detected based on break of excitation/inhibition balance. The method achieved 92.98% sensitivity, 0.16 FP/h, 14.5 s detection delay for TLE patients. Excitation/inhibition ratio does not vary much during interictal for TLE patients. Advances in understanding of ictogenesis can be translated to enhance our algorithm.